PEMANFAATAN MEDIA SOSIAL UNTUK KOMUNIKASI PEMASARAN VIRGIN COCONUT OIL (VCO) MASYARAKAT LOMBOK-NUSA TENGGARA BARAT - Andriano, Stefanus; Harrison, Alfonso; Jessica, Theodora; Francessa, Cecilia (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2023)
The Covid-19 pandemic has been going on since 2020 and for two years has dealt a serious blow to the tourism industry in Indonesia. One step taken to increase the number of tourist visits is to set a long-term target which is expected to be achieved by 2024. Certain cultures have been developed to become the main pillars of replacing natural tourism, examples of which are woven cloth craft products produced by the Sasak tribe in Rembitan Village, Central Lombok, as well as Virgin Coconut Oil (VCO) which not only has various benefits, but is also produced directly. by residents of Selamat Village, North Lombok. The main focus in this community service project is to overcome obstacles where community groups in the area have limited knowledge and skills in marketing the products they produce. Based on this context, Titian Foundation partners invited the Community Service Team from the Communication Studies Program at the Indonesian Catholic University Atma Jaya Jakarta to collaborate in holding training on the use of social media and improving skills in using these platforms for marketing communications purposes. Taking place in two locations, two groups of craftsmen in two different villages finally learned about the importance of creating and utilizing social media as a marketing medium for craft products. After the training is complete, the community can regularly implement marketing communication activities to potential consumers through the use of social media under the supervision of the Titian Foundation ABSTRAK Pandemi Covid-19 berlangsung sejak 2020 dan selama dua tahun memberikan pukulan telak bagi dunia industri pariwisata di Indonesia. Satu langkah yang diambil untuk meningkatkan jumlah kunjungan wisatawan adalah menetapkan target jangka panjang yang diharapkan tercapai pada tahun 2024. Beberapa budaya tertentu dikembangkan menjadi pilar utama pengganti pariwisata alam, contoh di antaranya adalah produk kerajinan kain tenun yang dihasilkan oleh suku Sasak di Desa Rembitan-Lombok Tengah, serta Virgin Coconut Oil (VCO) yang tak hanya memiliki beragam manfaat, namun juga diproduksi secara langsung oleh warga Desa Pemenang-Lombok Utara. Fokus utama dalam proyek pengabdian masyarakat ini adalah mengatasi hambatan di mana kelompok masyarakat di daerah tersebut memiliki keterbatasan pengetahuan dan keterampilan dalam memasarkan produk-produk yang mereka hasilkan. Berdasarkan konteks tersebut, mitra Titian Foundation mengajak Tim Pengabdian Masyarakat dari Program Studi Ilmu Komunikasi Universitas Katolik Indonesia Atma Jaya Jakarta untuk bekerjasama dalam menyelenggarakan pelatihan penggunaan media sosial serta meningkatkan keterampilan menggunakan platform tersebut untuk keperluan komunikasi pemasaran. Bertempat di dua lokasi, dua kelompok pengrajin di dua desa berbeda akhirnya belajar mengenai pentingnya membuat dan memanfaatkan media sosial sebagai salah satu media pemasaran produk kerajinan. Setelah pelatihan selesai masyarakat bisa secara reguler menerapkan sebuah aktivitas komunikasi pemasaran kepada para calon konsumennya melalui pemanfaatan media sosial dibawah pengawasan Titian Foundation.